Domestic and family violence: intervention through social work practice (2021)
There is Domestic and Family Violence (DFV) for everyone, regardless of race, ethnicity, or socioeconomic status, as it includes threats or acts of physical or sexual assault, stalking, harassment, or psychological/emotional abuse. Women cannot practice their right to self-determination when subjected to DFV, which impacts many areas of their lives and choices. DFV has been raised to national attention by social workers by identifying risky behaviours, and increasing and strengthening protective factors through public awareness, programmes design, and delivery. Social workers can apply this public health approach through community education, practice, and programme administration. Based on this, the paper examined social work practice interventions in assisting both in preventing and managing DFV. The field has been involved in addressing domestic violence for many decades particularly in developed countries with little emphasis in Nigeria which the country can adopt apart from laws enacted to curb and manage the incidence. It recommended that Ministry of Social Welfare and Woman Affairs concerned with welfare of women and girl child should work together with social workers/social welfare officers at both public and private sectors to make wider sensitization projects to all areas through electronic and print media. Social workers can advocate for better domestic violence policies and services to ensure more awareness of violence against women and its consequences and through partnership with other organisations, such as faith-based organisations, schools, hospitals, businesses, law enforcement, criminal justice, and the military